1991
DOI: 10.1073/pnas.88.11.5061
|View full text |Cite
|
Sign up to set email alerts
|

cAMP response element-binding protein is activated by Ca2+/calmodulin- as well as cAMP-dependent protein kinase.

Abstract: a convergence point for synaptic activity acting through kinase A and impulse activity acting through Cam kinase. Together the two kinases could activate transcription in a synergistic manner, which could allow CRE-binding protein to couple short-term to long-term associative forms of synaptic plasticity.Studies of neuronal plasticity in vertebrates and invertebrates indicate that long-term changes in the functional properties of nerve cells are often accompanied by and perhaps mediated through changes in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
259
2
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(271 citation statements)
references
References 33 publications
(37 reference statements)
8
259
2
2
Order By: Relevance
“…In the absence of CaM, peptides were not detected in the gel (result not shown). In the presence of CaM, peptides from two regions of the SRY HMG domain showed an interaction: residues 57-80 (lane 1) and a second, weakly binding region, 131-144, which gave multiple bands (lane 9). No CaM binding was detectable with the other six SRY peptides (lanes [3][4][5][6][7][8].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the absence of CaM, peptides were not detected in the gel (result not shown). In the presence of CaM, peptides from two regions of the SRY HMG domain showed an interaction: residues 57-80 (lane 1) and a second, weakly binding region, 131-144, which gave multiple bands (lane 9). No CaM binding was detectable with the other six SRY peptides (lanes [3][4][5][6][7][8].…”
Section: Resultsmentioning
confidence: 98%
“…Many nuclear functions are under CaM control and some transcriptional activators are known to be modulated indirectly through CaM-dependent kinases [8,9]. CaM has more recently been shown to influence transcription by interacting directly with basic helix-loop-helix (bHLH) DNA binding proteins through differential inhibition of the DNA binding activity of these domains [10].…”
Section: Introductionmentioning
confidence: 99%
“…Because CREB is activated by PKA [32,33] and since CBP (CREB binding protein) is a coactivator for both CREB and ER [34][35][36], we examined whether CREB was involved in the synergistic activation of ER by E 2 and PKA. We found that CREB could enhance the activity of ER in CHO cells, and that when CREB was transfected into SK-BR-3 cells, we saw transcriptional synergy where this was not seen if CREB was not transfected into these cells.…”
Section: Introductionmentioning
confidence: 99%
“…We discuss the possible physiological implications of these results. miny, 1989;Dash et al, 1991;Sheng et al, 1991;de Groot et al, 1993de Groot et al, , 1994Ginty et al, 1994). In particular, activation of transduction pathways independent from cAMP may also result in CREB phosphorylation, as for instance in PC12 cells upon NGF treatment (Ginty et al, 1994).…”
Section: Introductionmentioning
confidence: 99%